Insurance Fraud: A Criminological Approach (Archives of Criminology, 2008)
The text focusses on the criminological view of economic crime. The author draws attention to the characteristics of this crime and presents an in-depth division of economic offenders into professional, situational, and occasional offenders. The text also cites another well-known classification of economic offenders, dividing them into offenders from the upper, middle, and lower strata. Nevertheless, the main point of the considerations is the characteristic of insurance abuse and its offenders. Konrad Buczkowski concentrates on the reasons for the behaviour of these offenders, by dividing them into external and internal ones. He stresses that people who commit insurance fraud often feel wronged (e.g. by systemic conditions).In conclusion, Buczkowski claims that the analysis presented in the article confirms that it is impossible to create a universal ‘model’ of a perpetrator of economic crime. Among the sources of the phenomenon, he points, first of all, to the inconsistencyin the same elements that characterise economic offenders, with emphasis on white collar crime and those who decide to extort compensation to the detriment of an insurance company.